Protesting Human Life Amendment; Supporting Women's Right to Choice by State Building on Mariposa Mall - Watkins, Howard::::::::: (1981)
Protesters walking in large circle holding signs: "Choice is as American as Apple Pie" Nancy Bleile-Kratzer and ? Carrying American Civil Liberties Union banner